Comparison of facial morphometric analysis using CBCT volumetric rendering and digital photography. Issue 3 (May 2016) - Gage, C. Colby; Elo, Jeffrey A.; Sun, Ho-Hyun (Brian); McClendon, Grant D.; Azevedo, Bruno; Henson, Bradley S.
Abstract: Objective: Assess accuracy of facial morphometric analysis using 3-D CBCT volume rendered images for facial hard/soft tissue treatment planning using multi-clinician analyses across various training backgrounds. Methods: The 3-D CBCT and 2-D photographic image records of 25 subjects were evaluated in this study. Standard facial landmarks were identified independently by dental specialists on frontal and lateral images of the face. Facial proportions were calculated on both images and compared. Results: 3-D CBCT derived images were more accurate than 2-D photometric analysis when measuring upper and lower lip lengths in frontal view. 3-D CBCT derived images produced proportions comparable to 2-D photometric analysis in lateral view. Conclusions: Clinicians of different training backgrounds show higher consistency and accuracy in measurement of the lower facial third from the frontal aspect with 3-D CBCT derived images than with 2-D photographs. No statistical differences were observed from the lateral aspect. 3-D CBCT images eliminated errors caused by obfuscating features in the lower facial third.